2021
DOI: 10.3390/en14082272
|View full text |Cite
|
Sign up to set email alerts
|

Economic Impacts of Thailand’s Biofuel Subsidy Reallocation Using a Dynamic Computable General Equilibrium (CGE) Model

Abstract: For two decades, the Thai government has been promoting ethanol and biodiesel consumption through tax measures and price subsidies. Although this policy has substantially increased the consumption and production of biofuels, there is concern regarding its future fiscal burden. Due to fiscal constraints, the Thai government has planned to completely terminate the biofuel subsidy by 2022. This study aims at examining the economy-wide impacts of removing the biofuel subsidy and also conducting simulations of alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
2
2
0
Order By: Relevance
“…These obtained results are in accordance with those reported in previous publications using CGE models for examining the economy-wide impacts of biofuel policies in the case of Thailand [9,10]. Specifically, this study's simulation outcomes similarly showed that the expansion of biofuels could induce substitution effects on sectoral productions, leading to the manufacturing contraction of petroleum and natural gas.…”
Section: Conventional Gdp and Other Economic Impactssupporting
confidence: 91%
See 2 more Smart Citations
“…These obtained results are in accordance with those reported in previous publications using CGE models for examining the economy-wide impacts of biofuel policies in the case of Thailand [9,10]. Specifically, this study's simulation outcomes similarly showed that the expansion of biofuels could induce substitution effects on sectoral productions, leading to the manufacturing contraction of petroleum and natural gas.…”
Section: Conventional Gdp and Other Economic Impactssupporting
confidence: 91%
“…On the other hand, all participants in the biofuel supply chain (e.g., tapioca, sugarcane, and oil palm plantations) could benefit from this structural shift. Likewise, the macroeconomic indicators obtained from this study's simulations align with those shown in Phomsoda et al [9] and Phomsoda et al [10], indicating the same range of variation in real GDP and the essential role of productivity improvement on inflation (i.e., the percentage change of CPI).…”
Section: Conventional Gdp and Other Economic Impactssupporting
confidence: 85%
See 1 more Smart Citation
“…In addition, the existence of externality problems also makes it impossible for the equilibrium price to accurately reflect the social costs and benefits 0 5,000 of biofuel ethanol production enterprises, thus resulting in "market failures." Therefore, in order to make up for the lack of market forces and correct the negative externalities of traditional oil enterprises and positive externalities of biofuel ethanol enterprises, it is necessary for the government to provide appropriate market intervention through policy support [1][2][3]. In practice, countries all over the world have introduced series of incentive policies to promote the development of biofuel ethanol industry.…”
Section: Introductionmentioning
confidence: 99%